The concept of the principle of payment of land-use - Говорун, Марія Дмитрівна (Problems of legality, 2018)
The article is dedicated to studying the essence of the principle of payment of land-use. The concepts of the principle, the principle of law, the principle of payment of land-use are analyzed, and also the main features of the principle of law such as normativity, universality, objectivity, and regulativity are described. A comparative analysis of the system of principles of law and the system of principles of legislation is made; the principle of payment of land-use is a part of the latter. In order to clarify the essence of this principle, the article focuses on the definition of "payment" and the structural elements of "payment" are marked. They are: the object (tangible or intangible goods for which the payment is made), the subject (the person who receives the necessary object for an accomplishment of a certain purpose), the payment (a monetary equivalent as a certain cost characteristics of the object), the purpose of such a payment (the subject takes possession of a particular object, gets into use of it or has it at his/her disposal). The value of land payment concerns not only replenishing the relevant local budgets and realization of the economic interests of the owner, but also the economic incentives for effective and rational land-use. Such conclusions can be drawn from the fact that the article about land payment is located in the chapter "Economic Incentives for Rational Use and Protection of Land" (the Land Code), which defines economic incentives for use and protection of land. This means that the local authorities, having a financial base, will be able to develop programs, whose objective will be to stimulate the owners and users of land to the proper use of land and its protection and also to finance fulfillment of such programs. Therefore, to a certain extent, payment for land can be considered as a kind of economic incentives, through which reproduction and increase of fertility and productivity of soils of the land plots will be implemented.